2018
DOI: 10.3147/jsfp.53.40
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Infection of <i>Renibacterium salmoninarum</i> in Hatchery-reared Juvenile Chum Salmon <i>Oncorhynchus keta</i> Resulted in Mass Mortalities after Long-term Rearing

Abstract: A previous study detected the major soluble antigen (msa) gene and its corresponding mRNA from Renibacterium salmoninarum (R.s.) in the kidney tissue and surface mucus of asymptomatic chum salmon fry and juveniles by nested PCR (nPCR), quantitative realtime PCR (qPCR) and a reverse transcription nested PCR assay (RT-nPCR) (Suzuki et al., 2017a). The chum salmon had been transferred from a hatchery in Hokkaido at the fry-stage (0.5 g) and reared at a wetlaboratory in the Salmon and Freshwater Fisheries Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The internal organs, in contrast to gills and skin, do not directly contact the outer environment, and thus may represent the organ’s specific symbiotic microbiome and provide important information. Already 30 years ago, a wide range of bacteria in kidney and liver of fish (Mudarris and Austin, ; Toranzo et al , ; Starliper and Tesk, ) was reported and in recent years more studies have focused on the presence of bacteria in apparently healthy fish internal organs (Pujalte et al , ; Suzuki, ). One explanation for the presence of bacteria in what should be considered a ‘sterile organ’ is the breakdown of immunological defence mechanisms as a result of stress, which enhances the presence of bacteria in immune system cells and in the blood’s circulation (Tort, ).…”
Section: Introductionmentioning
confidence: 99%
“…The internal organs, in contrast to gills and skin, do not directly contact the outer environment, and thus may represent the organ’s specific symbiotic microbiome and provide important information. Already 30 years ago, a wide range of bacteria in kidney and liver of fish (Mudarris and Austin, ; Toranzo et al , ; Starliper and Tesk, ) was reported and in recent years more studies have focused on the presence of bacteria in apparently healthy fish internal organs (Pujalte et al , ; Suzuki, ). One explanation for the presence of bacteria in what should be considered a ‘sterile organ’ is the breakdown of immunological defence mechanisms as a result of stress, which enhances the presence of bacteria in immune system cells and in the blood’s circulation (Tort, ).…”
Section: Introductionmentioning
confidence: 99%